Um olhar etnomatemático sobre conhecimentos do povo quilombola de Porto Leocárdio de São Luiz do Norte-GO - Jesus, William Sousa de (2023)
This dissertation is an ethnographic research, based on the perspective defended by Ubiratan D'Ambrosio referring to Ethnomathematics, which seeks to investigate the mathematics of the knowledge and actions of a people. The investigative locus is the knowledge presented in the daily tasks of the quilombola people belonging to the quilombola community of Porto Leocárdio. The remaining community consists of twenty-two families who live on the banks of the river das Almas in the municipality of São Luiz do Norte-GO. The research aims to investigate the knowledge used in the daily tasks of the Porto Leocárdio community, with the aim of identifying and understanding the Ethnomathematics knowledge present in their daily relationships. We tried to understand how the use of their own knowledge occurs, since the community shares situations in which it is necessary to deal with the environment in which they are inserted, showing as a spontaneous social factor of everyday life, situations such as classifying, comparing, measuring, organizing, counting and infer. We adopted as a reference to subsidize the analyzed processes the foundations of Ubiratan D'Ambrosio, Gelsa Knijnik, José Jorge de Carvalho, Tereza Vergani, José Roberto Linhares de Mattos, Eduardo Sebastiane Ferreira, among other researchers in Ethnomathematics. We chose to use a qualitative approach of an ethnographic nature, based on direct contact with the research object, to understand the organization of the Porto Leocárdio community and its cultural manifestations. However, we prioritize direct observation and detailed investigation of the facts in the place where they happen to produce a detailed description of the relationship between people and the culture they belong to, paying attention to the presentation of knowledge through actions carried out in everyday life. To this end, we adopted as methodological instruments, questionnaires, interviews, opinion polls, direct observations with the researched group and logbook for records. The research is relevant both in terms of theoretical, methodological, and empirical contributions, given the emergence of insisting on cultural and social valuation policies that are evident in the recognition and affirmation of the knowledge of each people.